Clinical Findings and Management of Diabetic Papillopathy - Gao, Eva (Canadian Journal of Optometry, 2021)
Diabetic papillopathy is an uncommon ocular manifestation of diabetes and is associated with a rapid decrease in hemoglobin A1c. The typical presentation of this condition tends to be asymptomatic with normal intracranial pressure. This case report reviews a 64-year-old Caucasian male presenting with diabetic papillopathy. Because this is a diagnosis of exclusion, magnetic resonance imaging, magnetic resonance venography, and lumbar puncture must be performed to rule out other possible causes of optic disc edema, including ischemia, infection, inflammation, increased intracranial pressure from space-occupying lesions, and idiopathic intracranial hypertension.